Numerical solution of the derivative linear goursat problem / Mohd Agos Salim Nasir and Ahmad Izani Md. Ismail - Nasir, Mohd Agos Salim; Md. Ismail, Ahmad Izani (2004)
Studies have been carried out on the effect on accuracy when different means are used to compute function values in the finite difference solution of the Goursat problem. One study found that the use of harmonic mean averaging resulted in more accurate results compared with arithmetic mean averaging whilst another study found the opposite to be the case. In this paper, we investigate this issue further by focusing on two Goursat problem involving a derivative terms.